Comparison the Effectiveness of Oxytocin and Misoprostol in Prevention of Primary Post-Partum Haemorrhage - Saira Ghafoor, Bibi Sara, Farkhanda Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Postpartum haemorrhage is one of the leading causes of maternal mortality. Maternal Mortality globally is estimated as 599.00 deaths per year, a ratio of 400 maternal deaths per 10,000 live births. The aim of this study was to compare the effectiveness of oxytocin and misoprostol in prevention of primary post-partum haemorrhage Material and Method: It was Randomized Controlled Trial, which was conducted in the department of Obstetrics and Gynaecology, Hospital, Peshawar, between 14th March 2020 to 22 April 2022). The sample size was 100(50 in each group) Using 4% of PPH in misoprostol group, 24% of PPH in oxytocin group, 95% confidence level and 90% power of test under WHO software for sample size determination. Results: A total of 100 patients of primary post-partum haemorrhage were observed, which were divided in two equal groups A & B. Patients in Group A were managed with misoprostol while patients in group B will be subjected to oxytocin. Gravida wise distribution shows that out of 50 patients 22(44%) were gravid less than or equal to one,18(36) patient have 2-5 and 10(20%) were more than 5 while group B contains 25(50%) less than or equal to one, 17(34%) patients 2-5 and 8(16%) have gravid more than 5. Gravida distribution among the groups was insignificant with p-value=0.802. Average age was 27.82 years+4.56SD with range of 20-36 years. Group A contained 13(26%) patients in less than or equal to 25 years, 30(60%) patients 26-35 years and 7(14%) patients having ages of more than 35 years. While group B contained 18(36%) patients in less than or equal to 25 years, 28(56%) in 26-35 years and 4(8%) patients with age more than 35 years. The age distribution among the group was also insignificant with p-value 0.429. Efficacy wise distribution was significant with p-value = 0.021. Group A showed 47(94%) efficacy while non-effective in 3(6%) patients. Similarly, Group B showed 39 (78%) efficacy while non effective in 11(22%) patients. The misoprostol has greater efficacy than oxytocin. Age wise distribution of drug-efficacy shows that efficacy was almost same in all age groups. The patients having less than or equal to 25 years of age have shown efficacy in 12(92.3%) patients while 1(7.7%) patients being non-effective. Patients with 26-35 years of age have shown efficacy in 28(93.3%) of patients and 2(6.7%) have shown no efficacy. Similarly, 7(100%) patients have shown efficacy and no patients have no efficacy, with age more than 36 years of age. The same pattern was followed in group B, although age wise efficacy was insignificant in both the groups with p-value=0.765 and 0.987 respectively. The prevention of PPH, particularly in resource poor settings, where PPH is the leading cause of maternal mortality The enormity of postpartum haemorrhage and the limitations in the use of oxytocin for the adequate preventive therapy were the basic rationales behind this study. Secondarily, our cultural setups of home deliveries have a marked role in grave morbidity as well as lack a consensus protocol for the choice of adequate preventive treatment of haemorrhage. Keeping in view the above mentioned factors, this study was conducted to compare the effectiveness of the per rectal misoprostol medication to the intramuscular oxytocin to control the blood loss as adequate preventive therapy. Conclusion: Misoprostol is more effective as compared to oxytocin in prevention of primary postpartum hemorrhage. Keywords: Primary Postpartum haemorrhage, Cervical tears, Vaginal tears, oxytocin, Misoprostol, efficacy